'I Am Powerful': Agency, Autonomy and Audacity in Sefi Atta's A Bit of Difference. Issue 2 (3rd July 2022) - Olufunwa, Harry
Abstract: This article examines Sefi Atta's A Bit of Difference from the perspective of the novel's seminal 'I Am Powerful' scene the multiple interpretations of which encapsulate the issues of feminine independence of thought and action which the novel portrays through Deola Bello, the main character. As aspiration, motto and model of ideal behaviour, 'I Am Powerful' is very significant to her situation as a black woman reacting to the various pressures of life in a major western metropolis, particularly her desire to engage in meaningful relationships and live a fulfilling life on her own terms, rather than those prescribed to her by others. The article refracts 'I Am Powerful' through the perspectives of agency, autonomy and audacity which serve as markers of Deola's growth. It is argued that each element marks a specific stage in her progression towards an increased self-awareness which incorporates a better understanding of the dilemmas, triumphs and challenges she encounters as a black woman in the diaspora.